프랜차이즈 스토어를 대상으로 한 소셜 빅데이터 분석 방법 - 김현규(Hyeon Gyu Kim) (한국컴퓨터정보학회논문지, 2021)
프랜차이즈 스토어를 대상으로 소셜 빅데이터 분석을 수행할 경우, 프랜차이즈에 속한 여러 분점의 리뷰들이 함께 수집될 수 있어 분석 결과가 왜곡될 수 있다. 이 경우 분석 정확도를 높이기 위해서는 분석 대상이 아닌 타 분점의 리뷰들을 적절히 필터링할 수 있어야 한다. 본 논문에서는 프랜차이즈 스토어들의 특성을 반영한 소셜 빅데이터 분석 방법을 제안한다. 제안 방법은 검색어 설정 방법과 리뷰 필터링 방법을 포함한다. 검색어 설정을 위해, 소상공인진흥공단에서 제공하는 공공데이터를 기반으로 검색에 필요한 지역명을 추출한다. 그리고 리뷰 필터링을 위해, 네이버 및 카카오 등에서 제공하는 검색 API를 이용하여 프랜차이즈 분점 정보를 알아내고, 분석 대상이 아닌 타 분점의리뷰들을 필터링하는데 이용한다. 제안 방법의 검증을 위해 온라인에서 수집된 실제 리뷰를 대상으로 실험을 수행하였으며, 제안 방법의 리뷰 필터링 정확도는 평균 93.6%로 조사되었다. When conducting social big data analysis for franchise stores, reviews of multiple branches of a franchise can be collected together, from which analysis results can be distorted significantly. To improve its accuracy, it should be possible to filter reviews of other branches properly which are not subject to the analysis. This paper presents a method for social big data analysis which reflects characteristics of franchise stores. The proposed method consists of search key configuration and review filtering. For the former, the open data provided by Small Business Promotion Agency is used to extract region names for collecting reviews more accurately. For the latter, open search APIs provided by Naver or Kakao are used to obtain franchise branch information for filtering reviews of other branches that are not subject to analysis. To verify performance of the proposed method, experiments were conducted based on real social reviews collected from online, where the results showed that the accuracy of the proposed review filtering was 93.6% on the average. KCI Citation Count: 0